Socioeconomic inequalities in diabetes prevalence: the case of Egypt between 2008 and 2015 - Sahar Sidahmed; Siegfried Geyer; Johannes Beller (BMC, 2023)
Abstract Background There is a steady increase in diabetes prevalence globally and many studies imply that high socioeconomic status (SES) is inversely related to diabetes prevalence. However, there is scarcity in literature from countries like Egypt regarding this topic. Methods This study aims to investigate prevalence of diabetes in Egypt between 2008 and 2015, and the effect of SES. Diabetes prevalence -based on self-reports of past diagnosis- was measured using two datasets Egypt DHS 2008 (10,917 participants) and EHIS 2015 (16,485 participants). Logistic regression and odds ratios (ORs) with 95% confidence intervals (CIs) were applied for diabetes controlling for age, gender, educational level, employment status and place of residence. Extend of difference in diabetes prevalence between the two time points was measured by combining the two datasets using the EDHS 2008 as reference. Results Diabetes prevalence was higher in 2015 (4.83%) compared to 2008 (3.48%). It was more in women at both time points (4.08% and 5.16% in 2008 and 2015 respectively) compared to men (2.80% and 4.43% in 2008 and 2015 respectively). Older age and living in urban areas were positively related to diabetes prevalence at both time points. Men had a significant higher chance of developing diabetes in 2015 (OR = 1.45, p-value = 0.001). Men with higher education had higher chance of developing diabetes (OR = 1.76), in contrast to women (OR = 0.59). Employment decreased the chance of developing diabetes for men (OR = .72), but had minimal effect on women (OR = 1.06). Conclusion Diabetes prevalence in Egypt has increased between the years 2008 and 2015 and evident social inequalities were found. Women had more diabetes than men and were more affected with low SES. Unlike women, highly educated men had higher chance of developing diabetes in 2015 compared to 2008. This might be attributed to behavioral and sociocultural factors.